Computational Methods for Protein Structure Prediction and Modeling Volume 2: Structure Prediction - Xu, Ying.; Xu, Dong.; Liang, Jie.; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
Volume 2 of this two-volume sequence focuses on protein structure prediction and includes protein threading, De novo methods, applications to membrane proteins and protein complexes, structure-based drug design, as well as structure prediction as a systems problem. A series of appendices review the biological and chemical basics related to protein structure, computer science for structural informatics, and prerequisite mathematics and statistics.
Protein Structure Prediction by Protein Threading -- De Novo Protein Structure Prediction -- Structure Prediction of Membrane Proteins -- Structure Prediction of Protein Complexes -- Structure-Based Drug Design -- Protein Structure Prediction as a Systems Problem -- Resources and Infrastructure for Structural Bioinformatics.
Keywords: Physics; Proteomics; Bioinformatics; Biophysics; Biological physics; Physics; Biophysics and Biological Physics; Proteomics; Bioinformatics; Electronic books